Pengaruh Intensitas Penyinaran dan Komposisi Media Tanam terhadap Pertumbuhan Aglaonema Varietas Dud Unyamanee - Fitria Jasmine; Retni Mardu Hartati; Erick Firmansyah (Program Studi Agroteknologi INSTIPER, 2023)
Aglaonema is one of the horticultural agricultural commodities in the ornamental plant group which has high potential and high value. The community has several aglaonema, but some of them have pale leaves and don't grow well. Therefore, research is needed to find the right technical culture information for aglaonema growth. The purpose of this research is to find out how Aglaonema var. respond to growth. Dud unnyamanee on the composition of the planting medium and the irradiation intensity. This research was conducted in divided plots with a completely randomized design/CRD 2 factors using polybags measuring 20x20 cm. The first factor was the irradiation intensity (main plot) which can be as high as 15 percent using 85% paranet shading or as low as 30 percent with 70 percent paranet shading. The second factor was the method of making the planting medium (sub-plots): compost, husk charcoal, cocopeat. For each parameter, the findings show that there was no interaction between irradiation intensity and growing medium composition. It was possible that each treatment had a different effect. In the number of leaves parameter, the irradiation intensity of 15% showed that the number of leaves was greater than the intensity of 30%. The number of stomata which were primarily used for gas exchange such as carbon dioxide (CO2) that plants need during photosynthesis could be affected by shade. Soil levels of N, P, and K nutrients also affected the number of leaves. All observed parameters did not show a significant difference in the treatment of the planting medium composition.